ANALYSIS OF POLYMORPHIC VARIANTS OF CYTOKINE GENES IN PATIENTS WITH HIV INFECTION - N. A. Sukhalentseva; I. O. Naslednikova; A. S. Chernov; V. I. Reshetnikov; O. I. Urazova; V. V. Novitsky; M. V. Urozaeva; E. N. Chernova; E. L. Nikulina; O. V. Voronkova (Медицинская иммунология, 2014)
Abstract. A distribution mode for allelic variants of cytokine genes was evaluated in 184 patients with slow viral infections, including 97 patients with chronic herpetic infection and 87 HIV-infected patients. Using modern methods of immunogenetics, we have found that relative risks of recurrent course and poor outcome of infection are positively associated with AA promoter region genotype and AA promoter genotype of +874 A/T polymorphism in the IFNG gene. Immunogenetic factors associated with protective effect in slow virus infections, include G allele of TNFA gene (G-308A SNP), and T allele/TT genotype of promoter region in  the IFNG gene (+874 A/T SNP). (Med. Immunol., 2011, vol. 13, N 1, pp 79-82)